Valois, a component of the nuage and pole plasm, is involved in assembly of these structures, and binds to Tudor and the methyltransferase Capsuleen. - Anne, J.; Mechler, B.M. (Development, 2005)
Using the Capsuleen (Csul) methyltransferase as bait in the yeast two-hybrid system, we have identified a novel Drosophila protein containing multiple WD repeats and encoded by the valois (vsl) gene, which acts in pole plasm function. Vls is homologous to human MEP50, which forms a complex with the PRMT5 methyltransferase--the human homologue of Csul. We found that Vls localizes to the nuage in the nurse cells and to the pole plasm in the oocyte. Moreover vls is required for the synthesis and/or stability of Oskar and the localization of Tudor (Tud) in both the nuage and at the posterior pole of the oocyte. Furthermore, we show that Vls and a fragment of Tud interact directly in binding assay. As the PMRT5/MEP50 complex is involved in ribonucleoprotein complex assembly, we hypothesize that the Vls complex may play a similar function in assembling the nuage in nurse cells and the polar granules in the oocyte.